Oral diffuse B-cell non-Hodgkin's lymphoma associated to Gorlin-Goltz syndrome: A case report with one year follow-up - Cláudio M Pereira; Ana Paula M Lopes; Alexandre J Meneghini; Alberto F Silva; Tessa de L. Botelho (Wolters Kluwer Medknow Publications, 2011)
Nevoid cell carcinoma syndrome or Gorlin-Goltz syndrome is an autosomal dominant disorder characterized by multiple basal cell carcinoma, multiple keratocyst tumors, and skeletal anomalies. The Gorlin-Goltz syndrome has been associated with numerous benign and malignant neoplasms. The authors describe a case of Gorlin-Goltz syndrome in association with non-Hodgkin's lymphoma. To the best of our knowledge, this is the second case described in the English literature.